Empathy in the phenomenological tradition - Asif Ehsani; Hassan Reza Khawari (حکمت اسرا)
In the past few years, there has been a lively debate on whether and how phenomenology cancontribute to social cognition research. Notably, some have doubted whether first-personal,phenomenological descriptions of intersubjective experience and interaction can support ordisconfirm certain theories about social cognition (e.g., Spaulding 2015). In contrast to such anassessment, the aim of the present contribution will be to present an overview of the rich anddetailed discussion of empathy found in the phenomenological tradition, focussing particularlyon those aspects of this discussion that we believe to contain important and subtle insights ofcontemporary relevance.Our approach in the following will be as follows. First, we will examine the account ofempathy offered by the two phenomenologists whose writings on the topic we take to bethe richest and clearest, Husserl and Stein, explicating their arguments for the claims that(i) empathy is a sui generis mode of intentional experience, (ii) the basic form of empathycan nevertheless be characterised as perception-like, and (iii) that a higher-order form ofempathy is a more imagination-like way of understanding other persons from their ownpersonal perspective.